Cultural variation in communal versus exchange norms Implications for social support. [article]. - Miller, Joan G.; Akiyama, Hiroko
Whereas an interdependent cultural view of self has been linked to communal norms and to socially supportive behavior, its relationship to social support has been called into question in research suggesting that discomfort in social support is associated with an interdependent cultural view of self (e.g., Taylor et al., 2004). These contrasting claims were addressed in 2 studies conducted among Japanese, Indian, and American adults. Assessing everyday social support, Study 1 showed that Japanese and Americans rely on exchange norms more frequently than Indians among friends, whereas American rely on exchange norms more frequently than Indians and Japanese among siblings. Assessing responses to vignettes, Study 2 demonstrated that Japanese and Americans rely more frequently on exchange norms than Indians, with greatest relational concerns and most negative outlooks on social support observed among Japanese, less among Americans, and least among Indians. Results further indicated that relational concerns mediated the link between exchange norms and negative social support outlooks. Supporting past claims that relational concerns explain cultural variation in discomfort in social support (e.g., Kim, Sherman, & Taylor, 2008), the findings underscore the need to take into account as well the role of exchange norms in explaining such discomfort. The findings also highlight the existence of culturally variable approaches to exchange and call into question claims that discomfort in social support can be explained in terms of the global concept of an interdependent cultural view of self. -- (from the authors)
Keywords: Psychology-Periodicals.; Collectivism; Communal norms; Culture; Exchange norms; Social support